Design and analysis of optical system of semi-active laser seeker - Pu, Xiaoqin; Du, Yawen; Dong, Quanlin (Journal of physics. Conference series, 2020)
The laser seeker is an important part of navigation guided weapons. The working principle of the laser seeker was expounded, and the optical system of the seeker was designed according to the system index requirements. Its optical system is mainly composed of a receiving optical lens combination and a four-quadrant detector. According to the system performance and technical indicators such as the detection distance of the seeker, the receiving clear aperture, and distortion, the laser imaging spot diameter and the center position range were simulated. The optical system model was established by using CODE-V software. And the spot quality was optimized and evaluated through distortion, trace map, and radial envelope energy curve. Finally, an optical system that satisfies the requirements is designed, and the spot imaging quality is great, and the angular tracking accuracy reaches 0.10° / s.